2020
DOI: 10.21203/rs.3.rs-44069/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of FBXL19-AS1 in hepatocellular carcinoma by lncRNA–miRNA–mRNA network analysis and its diagnostic and prognostic value

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common neoplastic diseases worldwide. Available biomarkers are not sensitive enough for the diagnosis of HCC, seeking new biomarkers of HCC is urgent and challenging. The purpose of this study was to investigate the role of F-box and leucine-rich repeat protein 19-antisense RNA 1 (FBXL19-AS1) through competing endogenous RNA (ceRNA) network and its diagnostic and prognostic value in HCC.Methods: A comprehensive strategy of genomic data mining, bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A study conducted by Jiang et al has indicated that LncRNA FLVCR1-AS1 may promote proliferation, migration, and invasion of osteosarcoma cells by regulating the Wnt/β-catenin pathway [ 43 ].…”
Section: The Effect Of Flvcr1-as1 On Several Cancersmentioning
confidence: 99%
See 3 more Smart Citations
“…A study conducted by Jiang et al has indicated that LncRNA FLVCR1-AS1 may promote proliferation, migration, and invasion of osteosarcoma cells by regulating the Wnt/β-catenin pathway [ 43 ].…”
Section: The Effect Of Flvcr1-as1 On Several Cancersmentioning
confidence: 99%
“…An experimental study conducted by Hao et al illustrated that the LncRNA FBXL19-AS1/miR-342-3p pathway plays a crucial function in the proliferation, migration, and invasion of Huh7 cells treated by flavonoids of Sophorae Fructus [ 42 ]. Furthermore, another study revealed a positive correlation between FBXL19-AS1 TNM stage and poor prognosis of HCC patients, where FBXL19-AS1 acts as a regulation agent, controlling HCC-associated pathways, including cell cycle, microRNAs in cancer, viral carcinogenesis via ceRNA network [ 43 ]. Consequently, this lncRNA may be considered a diagnostic and prognostic biomarker [ 44 ].…”
Section: The Effect Of Fbxl19-as1 On Several Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…This manuscript has been released as a pre-print at Research Square, (He DD, Zhang XK, Zhu XY, et al.) ( 58 ).…”
Section: Acknowledgmentsmentioning
confidence: 99%